Effect of effleurage massage technique with postnatal massage technique on afterpains in postpartum mothers - Maidina Putri; Bima Suryantara; Siti Saidah Nasution (Science Midwifery, 2023)
The effect between Effleurage Massage Technique and Postnatal Massage Technique on afterpains in postpartum women at BPM Hj. Rismala Kisaran Asahan Regency in 2023. Afterpains are pain caused by uterine contractions after labor and can interfere with maternal comfort. This study used a comparative research design with a Two-Group Pretest-Posttest Design Without Control approach. The population of this study consisted of 64 postpartum women who experienced afterpains at Hj. Rismala Independent Practice Midwife in Kisaran, Asahan Regency. The sampling technique was carried out by total sampling, where 32 respondents were in the Effleurage Massage Technique group and 32 respondents were in the Postnatal Massage Technique group without a control group. Data analysis using the Mann-Whitney test showed that the Postnatal Massage Technique group had a more significant effect in reducing afterpains compared to the Effleurage Massage Technique group, with a significance value of p <0.05. Thus, the conclusion of this study is that the Postnatal Massage Technique is more effective in reducing afterpains in postpartum women compared to the Effleurage Massage Technique.